From global campaign to global commitment: The World Health Assembly's Resolution on epilepsy. (22nd September 2015) - Covanis, Athanasios; Guekht, Alla; Li, Shichuo; Secco, Mary; Shakir, Raad; Perucca, Emilio
Summary: Tuesday May 26, 2015, will be remembered as an historic day in the fight against epilepsy. On that date, the World Health Assembly approved unanimously the Resolution on the "Global Burden of Epilepsy and the Need for Coordinated Action at the Country Level to Address its Health, Social and Public Knowledge Implications, "1 which urges Member States to implement a coordinated action against epilepsy and its consequences. This event, which comes almost 20 years after the establishment of the Global Campaign against Epilepsy, is another landmark in the longstanding collaboration among the World Health Organization (WHO), the International League Against Epilepsy (ILAE), and the International Bureau for Epilepsy (IBE) in addressing the needs of people with epilepsy. It also acted as a catalyst for other professional societies, including the World Federation of Neurology (WFN), to join forces in promoting a common action against epilepsy. The Resolution did not happen by chance, but came at the end of a long journey that involved the hard and tireless work of many dedicated individuals around the globe.